Antibacterial sensitivity of E.coli isolated from milk and milk products in Jabalpur, India - Tripathi, Shweta; Sarkar, Nandita (Indian Journal of Dairy Science, 2020)
Milk and milk products are an essential element of the diet. Apart from its nutritional value, it can also serve as a carrier for multidrug-resistant bacteria attributed to many infectious diseases. The present study was conducted to detect antibiotic-resistant bacteria from milk and milk products (Raw milk, pasteurized milk, and cottage cheese) marketed in Jabalpur city of Madhya Pradesh, India. A total of 640 samples of pasteurized milk, raw milk, and cottage cheese were collected in a sterile container from different dairies and shops of Jabalpur city. Immediately after collection, samples were brought to the microbiology lab within 1 hour. The Escherichea coli were isolated from milk and cottage cheese samples, based on cultural and molecular tests. These isolates were further subjected to antibacterial susceptibility against commonly used antibiotics by the disk diffusion methods. Out of 640 samples examined, 118 (18.44%) were positive for Escherichea coli. The highest isolation of Escherichea coli was from cottage cheese (32%), followed by raw milk (22.5%) and pasteurized milk (0%). Antibiotic susceptibility profile showed that Escherichia coli were resistant for nitrofurantoin (61.8%), nalidixic acid (37.2%) and cefotaxime (30.50%). The analysis showed that 89.8 % of isolates showed multidrug resistance comprising 2-3 antimicrobials. The presence of Escherichea coli with multiple antibiotic resistances poses a significant threat to public health and food safety. These findings stress the need for better sanitation practices in the production and consumption of milk and milk products and strict monitoring of uses and misuses of antibiotics in humans and food animals.